Revolutionary summer [compact disc, unabridged] : the birth of American independence - Ellis, Joseph J. (Random House Audio, 2013)
Joseph J. Ellis' focus: the summer of 1776, the most dramatic few months in the story of our country's founding. The thirteen colonies came together and agreed to secede from the British Empire. At the same time, the British dispatched the largest armada ever to cross the Atlantic; it cruised off the coast of Staten Island in early July.